Experimental determination of thermal conductivity and permeability of 3-D printed structures - Tan, Wei Siong (2019)
This report presents the determination of the effective thermal conductivity of novel porous structures using a linear heat conduction test facility. The steady-state heat conduction measurement technique was employed, and the accuracy of the setup was validated using a reference aluminium specimen where a deviation in experimental results of not more than 9% was obtained. The heat losses to the surroundings were also minimised to ensure that the one-dimensional heat conduction assumption through the test specimens is valid. Subsequently, designs of novel porous structures were explored. Based on the commonality of use, a set of lattice Octet-truss structures were fabricated, and their effective thermal conductivities were determined. The effective thermal conductivities of these structures were analysed and compared to other sets of porous structures, namely the Rhombi-octet lattice and the H-shaped structure, which were designed based on Constructal theory. The comparisons were made based on a fixed porosity of 0.85 and the results showed that the effective thermal conductivities of the Octet-truss structure are 2 times smaller than the Rhombi-octet lattice and about 5 times smaller than the H-shaped structure. In addition, this report also explored the use of the fluid’s diffusion coefficient to determine the permeability of the designed Octet-truss structures. A new test facility was designed and developed where the change in the diffusion coefficient of the salt solution in the porous structure was determined over time. This method of experimentation is highly different from the standard pressure drop tests for the permeability determination of porous structures. The permeability of the Octet-truss was determined but there was no clear trend with different porosities, and its permeability values are systematically smaller than the modelled permeability. The improvement of the test-rig is recommended in order to attain a more accurate experimental data with the permeability test-rig.